1996
DOI: 10.1093/biolreprod/54.6.1261
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Abundance of Arginine and Ornithine in Porcine Allantoic Fluid1

Abstract: The concentrations of free arginine, ornithine, and glutamine in porcine allantoic and amniotic fluids were determined on Days 30,35, 40, and 45 of gestation. Arginine and ornithine were the most abundant amino acids in allantoic fluid on Days 35-40 and 45 of gestation, respectively. Arginine and ornithine nitrogen accounted for 40%, 50%, and 55% of the total free alpha-amino acid nitrogen in allantoic fluid on Days 35, 40, and 45 of gestation, respectively. Glutamine was the most abundant amino acid in amniot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 17 publications
3
56
0
1
Order By: Relevance
“…This positive result is consistent with the presence of unusually high concentrations of amino acids in the arginine family in porcine allantoic fluid at the stage of blastocyst expansion and implantation in vivo (Wu et al, 1996;Gao et al, 2012) and of an increase in endometrial angiogenesis between Days 13 and 18 of gestation (Keys et al, 1986). Furthermore, arginine stimulates the AKT1-mTOR/FRAP1-RPS6K-RPS6 cell signaling pathways to increase proliferation and migration of porcine (Kong et al, 2012) and ovine (Kim et al, 2011) trophectoderm cells during peri-implantation period.…”
Section: L-argininesupporting
confidence: 81%
See 1 more Smart Citation
“…This positive result is consistent with the presence of unusually high concentrations of amino acids in the arginine family in porcine allantoic fluid at the stage of blastocyst expansion and implantation in vivo (Wu et al, 1996;Gao et al, 2012) and of an increase in endometrial angiogenesis between Days 13 and 18 of gestation (Keys et al, 1986). Furthermore, arginine stimulates the AKT1-mTOR/FRAP1-RPS6K-RPS6 cell signaling pathways to increase proliferation and migration of porcine (Kong et al, 2012) and ovine (Kim et al, 2011) trophectoderm cells during peri-implantation period.…”
Section: L-argininesupporting
confidence: 81%
“…Concentrations of glutamine are highest among amino acids in fetal tissues and maternal placenta (Self et al, 2004), and there are increased concentrations of glutamine in allantoic fluid in the second third of gestation (Wu et al, 1996), which highlights the importance of glutamine during that stage of rapid placental and fetal growth.…”
Section: Glutaminementioning
confidence: 98%
“…AFAAs are interconvertible via complex interorgan metabolism in most mammals, including pigs . Wu et al (1996b) have shown an unusual abundance of arginine and ornithine in porcine allantoic fluid from 35 to 40 days of pregnancy, that is, the period of rapid placental growth. Glutamine was the most abundant amino acid in the amniotic fluid during the early fetal stage of pregnancy (days 30 to 45) and was also abundant in the allantoic fluid.…”
Section: Sow Nutrition As An Opportunity To Improve Within-litter Unimentioning
confidence: 99%
“…We discovered an abundance of Arg in porcine allantoic fluid during early gestation (Wu et al, 1995(Wu et al, , 1996. Arginine and ornithine account for 50 and 55% of the total alpha amino-acid nitrogen (the sum of nitrogen in 伪-amino acids) in porcine allantoic fluid on days 40 and 45 of gestation, respectively.…”
Section: Argininementioning
confidence: 99%
“…The unusual abundance of arginine in porcine allantoic fluid during early pregnancy and its important physiological functions in survival and growth of the conceptus (see Wu et al, 1996) led to a study by Mateo et al (2007) to determine the effects of dietary supplementation of arginine on reproductive performance of pregnant gilts. Dietary supplementation with 0.83% arginine (as 1.0% arginine-HCl; 16.6g arginine/sow per day) between days 30 and 114 of gestation increased the number of live-born piglets by 2 per litter and litter birth-weight by 24% (Mateo et al, 2007).…”
Section: Argininementioning
confidence: 99%